2011
DOI: 10.3168/jds.2010-3372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidoreduction potential on aroma biosynthesis by lactic acid bacteria in nonfat yogurt

Abstract: The aim of this study was to investigate the effect of oxidoreduction potential (Eh) on the biosynthesis of aroma compounds by lactic acid bacteria in non-fat yogurt. The study was done with yogurts fermented by Lactobacillus bulgaricus and Streptococcus thermophilus. The Eh was modified by the application of different gaseous conditions (air, nitrogen, and nitrogen/hydrogen). Acetaldehyde, dimethyl sulfide, diacetyl, and pentane-2,3-dione, as the major endogenous odorant compounds of yogurt, were chosen as tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 38 publications
5
44
0
Order By: Relevance
“…The authors also demonstrated that oxidative Eh conditions clearly increased the production of aroma compounds [51]. These results are consistent with the bibliography.…”
Section: Impact On Aroma Biosynthesis By Lactic Acid Bacteriasupporting
confidence: 80%
See 4 more Smart Citations
“…The authors also demonstrated that oxidative Eh conditions clearly increased the production of aroma compounds [51]. These results are consistent with the bibliography.…”
Section: Impact On Aroma Biosynthesis By Lactic Acid Bacteriasupporting
confidence: 80%
“…Furthermore, during storage, different profiles were observed for the four aromas depending on the Eh conditions [51]. Under oxidizing conditions (+170 to +245 mV), the concentration of acetaldehyde was relatively stable during storage, which is in accordance with the literature [9,55,56] and the concentration of dimethyl sulphide was also stable.…”
Section: Impact On Aroma Biosynthesis By Lactic Acid Bacteriasupporting
confidence: 78%
See 3 more Smart Citations